Synaptotagmin-11 deficiency mediates schizophrenia-like behaviors in mice via dopamine over-transmission - Yang Chen; Yuhao Gu; Bianbian Wang; Anqi Wei; Nan Dong; Yong Jiang; Xiaoying Liu; Li Zhu; Feng Zhu; Tao Tan; Zexin Jing; Fenghan Mao; et al. (Nature Communications)
Abstract Schizophrenia is a severe neuropsychiatric disease, but the initiation mechanisms are unclear. Although antipsychotics are effective against positive symptoms, therapeutic interventions for negative symptoms are limited due to the lack of pathophysiological mechanisms. Here we identify synaptotagmin-11 (Syt11) as a potential genetic risk factor and dopamine over-transmission as a mechanism in the development of schizophrenia. Syt11 expression is reduced in individuals with schizophrenia but restored following the treatment with antipsychotics. Syt11 deficiency in dopamine neurons in early adolescence, but not in adults, leads to persistent social deficits and other schizophrenia-like behaviors by mediating dopamine over-transmission in mice. Accordingly, dopamine neuron over-excitation before late adolescence induces persistent schizophrenia-associated behavioral deficits, along with the structural and functional alternations in the mPFC. Notably, local intervention of D2R with clinical drugs presynaptically or postsynaptically exhibits both acute and long-lasting therapeutic effects on social deficits in schizophrenia mice models. These findings not only define Syt11 as a risk factor and DA over-transmission as a potential risk factor initiating schizophrenia, but also propose two D2R-targeting strategies for the comprehensive and long-term recovery of schizophrenia-associated social withdrawal.